Անանուն հեղինակի «Աստուածածին կոյսն Մարիամ» տաղը - Մուշեղյան, Աստղիկ
Among the medieval Armenian sacred chants, the taghs dedicated to the Crucifixion of the Lord have a special place. A separate theme is the most dramatic episode of the Gospel of John (19։25-27) depicting the Mother of God together with the Only Begotten Son nailed to the Cross. Of the many taghs, only three have survived with musical component, and among them, the one entitled Our Lady Virgin Mary, which was included in the Holy Patarag (Liturgy) recorded by N. T‘ashchyan. Среди армянских средневековых духовных песнопений особое место занимают таги, посвященные Распятию Господа. Отдельной темой в них представлен наиболее драматичный эпизод из Евангелия от Иоанна (19: 25-27), изображающий Богоматерь и пригвожденного к Кресту Единородного Сына. Из многочисленных тагов до нас дошли лишь три сочинения с музыкальным компонентом. Среди них таг “Богородица Дева Мария”, вошедший в Св. Патараг (Литургию), составленный Н. Ташчяном.
Keywords: Արվեստ; Տաղերգություն